Clean energy, clean governance: A diagnostic framework for preventing corruption in indonesia’s energy transition - Elisabeth Medina Dewi Saraswati; Julius Ferdinand; Mochamad Agung Sasongko; Rika Krisdianawati (Komisi Pemberantasan Korupsi, 2026)
Indonesia’s energy transition involves large-scale infrastructure investment, complex procurement, regulatory uncertainty, fragmented oversight, and coordination among multiple public and private actors, conditions that structurally expose the transition to corruption risks. Yet existing governance frameworks often remain at the level of normative principles, or focus on sector-specific case studies, without translating anti-corruption safeguards into operational tools tailored to a specific country’s institutional context. This study addresses that gap by developing the Energy Transition Governance Framework (ETGF), an indicator-based diagnostic framework designed to assess governance quality and identify corruption vulnerabilities across Indonesia’s electricity transition. Using a qualitative, participatory framework-development approach that combines document analysis, iterative stakeholder validation through multistakeholder focus group discussions, and expert peer review, the study maps corruption risks across the renewable energy project lifecycle and synthesizes these findings with international governance benchmarks. The resulting framework is organized into three pillars, five dimensions, and 77 indicators applicable to both renewable energy expansion and fossil fuel retirement. ETGF is proposed as a diagnostic tool intended to support integrity-oriented oversight, although its practical effectiveness remains subject to future institutional adoption, data availability, and methodological refinement.